Physical Stress and Determinants of Shooting Performance Among Norwegian Special Forces Operators - Buskerud, Jan Erik; Abrahamsen, Frank Eirik; Solberg, Paul André (Frontiers in Psychology, 2022)
However, there is a lack of conceptual understanding of the factors influencing performance decrements in prone shooting. The present study examines how one can simulate a combat scenario by inducing acute physical stress, ultimately impacting one’s shooting performance (SP). The relationship between participants’ physical level and SP was measured in several ways. The SP of members of the Norwegian Navy Special Operations Forces (SOF) (N=30) was measured before and directly after acute exercise-induced stress caused by a 200-m uphill run (90% HRmax). Under acute physical stress, participants took less time to fire five rounds (total 15.5 ± 10.9 s faster), and the probability of hitting the target was unaffected (92%). In terms of more sensitive measures, score was significantly reduced and shot-group dispersion increased (64 ± 90 cm2, p<0.01, d=0.72), mainly due to increased vertical dispersion (2.5 ± 4.6 cm, p<0.01, d=0.53). Age, trait somatic anxiety and the Big Five Inventory item ‘openness’ explained 45.2% of the variance in shooting score in the pre-physical stress condition. In the post-physical stress condition, pre-test shooting score, the number of months deployed, and shooting time predicted 32.9% of the variance in shooting score. The change in SP (pre – post) showed the concentration disruption scale was the best predictor of the reduction in shot score (20.1%). From a practical point of view, maintaining the probability of hitting the target with reduced shooting time post-physical stress could be viewed as superior performance for SOF.